Customer oriented service and cost effectiveness: A trade-off relationship? - Zulnaidi Yaacob (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
This paper describes the effect of customer oriented service (COS) on cost effectiveness of local authorities. Although a plethora of evidence had been unearthed regarding the usefulness of COS, particularly in achieving customer satisfaction, the effect of COS on cost effectiveness is relatively less explored. While most previous studies were conducted in business firms, this present study tested the applicability of COS in achieving the objective of cost effectiveness by local authorities. As a public firm, they face great financial challenges due to the shrinking funds available. Instead of looking for new external funding, local authorities have to find alternative ways in managing their limited existing funds effectively and COS is one possible approach to alleviate this situation. In the execution of this study, data were collected using a questionnaire completed by 205 local authority managers. The findings of this study testified that COS was not a trade-off practice with the objective of cost effectiveness. This study also revealed that intensified COS would lead local authorities to benefit from higher cost effectiveness. The managerial implication of this study is that although COS is generally meant for use in customer satisfaction, it could also bring benefits for achieving better cost effectiveness.
Keywords: 330; customer oriented service; cost effectiveness; local authorities